2020
DOI: 10.1021/acs.jpclett.0c02991
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Potential Energy Surfaces of BrCN by Dissociative Electron Attachment

Abstract: State coupling certainly determines the topologic features of the molecular potential energy surface (PES) and potentially diversifies chemical reaction pathways. Here we report the new PESs of BrCN– in the low-lying electronic states that are distinctly different from the previous predictions in the short Br–CN bond region but validated by the high-resolution ion velocity imaging measurements of low-energy dissociative electron attachment (DEA) to BrCN. Besides the vibrating CN– ions produced in the fast Br–C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…In this work, we report an experimental evidence that the CN − ** species are produced in the DEA to BrCN, where the CN − yield is populated in the vibrational states ( ν ≤ 17) at the low electron attachment energy ( E e ), while the CN − ** produced at the high E e value is in the vibrationally or electronically superexcited states. In the previous studies, the CN − ** species cannot be identified in the CN − production efficiency curve 26 and the low vibrational-state ( ν < 9) CN − yields were found in the lower attachment energy range ( E e = 1.07–1.97 eV) 27 . Using the high-resolution time-sliced velocity map imaging (VMI) apparatus 27 30 , which was developed on the basis of our previous one 31 , 32 , we record the velocity images of the CN − /CN − ** yields in the higher E e range from 3.57 to 6.57 eV, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In this work, we report an experimental evidence that the CN − ** species are produced in the DEA to BrCN, where the CN − yield is populated in the vibrational states ( ν ≤ 17) at the low electron attachment energy ( E e ), while the CN − ** produced at the high E e value is in the vibrationally or electronically superexcited states. In the previous studies, the CN − ** species cannot be identified in the CN − production efficiency curve 26 and the low vibrational-state ( ν < 9) CN − yields were found in the lower attachment energy range ( E e = 1.07–1.97 eV) 27 . Using the high-resolution time-sliced velocity map imaging (VMI) apparatus 27 30 , which was developed on the basis of our previous one 31 , 32 , we record the velocity images of the CN − /CN − ** yields in the higher E e range from 3.57 to 6.57 eV, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Experiments. In our laboratory, anionic high-resolution velocity (or momentum) imaging has been realized [27][28][29][30] , owing to the application of a trochoidal electron monochromator. In the experiments, within a crossed-beam arrangement, the monochromatized pulsed electrons (with an energy spread about 100 meV here, along y axis) are guided to the reaction region with a homogenous magnetic field (70 G) which is produced with a pair of Helmholtz coils; then the anionic yields are pushed out, accelerated, and flying (along z axis) through the VMI lens system.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments . In our high-resolution VMI apparatus, a trochoidal electron monochromator is used to reduce the energy spread of thermally emitted electrons. The narrow energy spread can be maintained for the pulsed electron beam (along the y axis), which is essential for obtaining anion velocity images with a high resolution . The anion detector (in the x–y plane) consists of two multichannel plates and a set of delay-line anodes (commercially available from Roentdek, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The energy spread (100–150 meV) of the monochromatized electrons for the high-resolution VMI measurements is much smaller than that (500–600 meV) of the thermal electrons emitted directly from the filament, and it is not worsened seriously under the electron-pulsed mode . Using the high-resolution VMI apparatus, here we report an experimental study of the near-threshold DEA process of nitrogen dioxide [e – + NO 2 (X 2 A 1 ) → NO 2 – → NO (X 2 Π) + O – ( 2 P)]. This is the energetically lowest pathway and has an energy threshold ( E th ) of 1.65 eV .…”
mentioning
confidence: 99%
See 1 more Smart Citation